STUDI TENTANG TINGKAT PEMAHAMAN DAN KESADARAN PEDAGANG TERHADAP KETENTUAN TERTIB NIAGA: METROLOGI LEGAL, PERLINDUNGAN KONSUMEN, DAN LABEL IKLAN PANGAN STUDI KASUS PEDAGANG PASAR TRADISIONAL: BALUBUR TOWNSQUARE (BALTOS) KOTA BANDUNG - Yasri, Budi (Prodi Administrasi Publik FISIP UNPAS, 2020)
Trade is an important thing in social life. Therefore, regulations are made to support the safety and comfort aspects of both the seller and the buyer. These regulations include the UUML (Legal Metrology Law), the UUPK (Consumer Protection Act), and PP LIP (Government Regulations for Food Advertising Labels). To find out how successful these regulations can be assessed from the public's knowledge of the regulations that have been enacted. How much knowledge of the rules can be obtained from interviews conducted in the community. With interviews, it can be seen how successful the regulations were made both in quantity and quality. From the interviews, it was obtained that 50% of the public already knew and implemented the regulation.